B7-H3 targeted antibody-based immunotherapy of malignant diseases. (4th May 2021) - Michelakos, Theodoros; Kontos, Filippos; Barakat, Omar; Maggs, Luke; Schwab, Joseph H.; Ferrone, Cristina R.; Ferrone, Soldano
ABSTRACT: Introduction : Recent advances in immuno-oncology and bioengineering have rekindled the interest in monoclonal antibody (mAb)-based immunotherapies for malignancies. Crucial for their success is the identification of tumor antigens (TAs) that can serve as targets. B7-H3, a member of the B7 ligand family, represents such a TA. Although its exact functions and receptor(s) remain unclear, B7-H3 has predominantly a pro-tumorigenic effect mainly by suppressing the anti-tumor functions of T-cells. Areas covered : Initially we present a historical perspective on TA-specific antibodies for diagnosis and treatment of malignancies. Following a description of the TA requirements to be an attractive antibody-based immunotherapy target, we show that B7-H3 fulfills these criteria. We discuss its structure and functions. In a review and pooled analysis, we describe the limited B7-H3 expression in normal tissues and estimate B7-H3 expression frequency in tumors, tumor-associated vasculature and cancer initiating cells (CICs). Lastly, we discuss the association of B7-H3 expression in tumors with poor prognosis. Expert opinion : B7-H3 is an attractive target for mAb-based cancer immunotherapy. B7-H3-targeting strategies are expected to be highly effective and – importantly – safe. To fully exploit the diagnostic and therapeutic potential of B7-H3, its expression in pre-malignant lesions, serum, metastases, and CICs requires further investigation.